2010
DOI: 10.1016/j.jcrs.2009.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic prophylaxis and risk factors for intraoperative floppy-iris syndrome in phacoemulsification performed by resident physicians

Abstract: The incidence of IFIS was lower than previously reported. Use of prophylactic intracameral lidocaine-epinephrine did not reduce the incidence of IFIS. A preoperative dilated pupil diameter smaller than 6.5 mm was significantly associated with an increased incidence of IFIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 49 publications
3
35
0
1
Order By: Relevance
“…These factors, together with the surgeon's subjective perception of the degree of severity of IFIS, especially in mild cases, may help explain the widely variable incidences and severity of IFIS reported in the literature. 3,21,22 With respect to IFIS prediction by pharmacologically dilated pupil size, such a possibility seems viable on the basis of our results. In general, preoperative and postoperative measurements taken with computerized pupillometer or calipers appear to be inversely related to the incidence and severity of IFIS.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…These factors, together with the surgeon's subjective perception of the degree of severity of IFIS, especially in mild cases, may help explain the widely variable incidences and severity of IFIS reported in the literature. 3,21,22 With respect to IFIS prediction by pharmacologically dilated pupil size, such a possibility seems viable on the basis of our results. In general, preoperative and postoperative measurements taken with computerized pupillometer or calipers appear to be inversely related to the incidence and severity of IFIS.…”
Section: Discussionmentioning
confidence: 79%
“…In a study of cataract extractions performed by resident physicians, the reported incidence of posterior capsule rupture and vitreous loss was 7.4% in patients taking tamsulosin compared with 1.8% in patients not taking tamsulosin. 22 Even for experienced surgeons, the rate of vitreous loss during cataract surgery in patients taking tamsulosin ranges from 0.6% for high-volume surgeons to 7.0% and 12.0% in United States and United Kingdom surveys, respectively. 1,13,21,22 However, when IFIS is anticipated and proper management strategies are used, the outcome is favorable and the complication rate is low for both skilled surgeons and residents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations